STUDI KELAYAKAN UNDERPASS CANGUK, KOTA MAGELANG, JAWA TENGAH: Feasibility Study of the Canguk Underpass, Magelang City, Central Java - Darmadi (FTSP Universitas Jayabaya, 2021)
This project is part of the effort of the Government of Indonesia in implementing theAccelerating Infrastructure Delivery through better Engineering Services Project (ESP) thatwill help meeting the infrastructure development objectives of the MPWH’s SectorDevelopment Plan (SDP), 2015-2019 and beyond. Several surveys were carried out to supportthe analysis of this study. The surveys include a topographical survey, road conditions survey,hydrology conditions, geotechnical investigation, and traffic surveys. From the results of theeconomic study, it gives an Economic Internal Rate of Return value of 37.86% which exceedsthe annual interest rate of 12% so it is said to be very feasible to build.